Exploration of tuna fish (Thunnus sp) skin waste as a burn wound treatment material using the Gamma Irradiation Method - Mahgfirah, Indria; Anhar, T. Faizul; Yusmianda, Yusmianda (Acta Aquatica: Aquatic Sciences Journal, 2025)
Tuna (Thunnus sp) is a fish with high economic value, both in the export community and local consumption (Fernandez, 2021). The amount of tuna (Thunnus sp) production increases every year. The increasing amount of fishery production and the development of the fishery product industry have caused a lot of fishery waste to be disposed of without processing. Waste from fishery product processing reaches 20-60% of the raw materials. Waste from fishery products processed with tuna as the raw material consists of 17% head, 20% skin, 5% offal, 4% bones, and 2% fins. In general, tuna skin is thrown away without further processing. However, tuna skin is a good source of collagen and does not cause bovine spongiform encephalopathy (BSE). Collagen, which provides 30% of the total protein content, is the most abundant fibrous protein in animals. Collagen plays an important role in regulating the wound-healing phase. This study used the Cobalt-60 gamma irradiation method with a dose of 10 kGy. The results of this study are with bacterial tests, tuna fish powder that has undergone gamma irradiation with a bacterial contaminant value of 0.19 x 103, and mold testing with a value of 0.00 x 103 with a pH of both 6.78. Functional groups of tuna fish skin collagen include Amide A found in the absorption region of 3330 cm-1, Amide B found in the absorption region of 2924 cm-1, Amide I found in the absorption region of 1640 cm-1, Amide II found in the absorption region of 1406 cm-1, and Amide III found in the absorption region of 1242 cm-1.Keywords: Collagen; Gamma Irradiation; Tuna Fish Skin; Waste